Stability Constraints of ROV-Coordinated Hole Drilling on Shipwrecks - Dongjun GUO; Xuyang WANG (水下无人系统学报)
Remotely operated vehicle(ROV)-coordinated hole drilling on shipwrecks is a key technical component for achieving underwater drilling and oil extraction integration. Currently, research on this control scenario in the engineering field is limited, and effective methods for stabilizing the pose of ROV-coordinated hole drilling on shipwrecks are lacking. This paper addressed the pose stability requirements during the ROV-coordinated hole drilling process on a shipwreck. By drawing parallels with the stability principles of ground-based equipment, a stability criterion for ROV-coordinated hole drilling on shipwrecks was established. Based on this criterion, a thrust correction algorithm was proposed. By modifying the thrust of each thruster, the force state of the collaborative system met the stability criterion, thereby achieving the stability constraints for the collaborative system’s pose. Simulation results show that the proposed stability constraint method can effectively maintain the pose stability of the collaborative system during the operation. In terms of stability, compared with the pre-correction state, the collaborative system transitions from an unstable constraint state to a stable constraint state, fully verifying the effectiveness and feasibility of the stability constraint method proposed in this study.